1998
DOI: 10.1016/s0014-5793(98)01257-5
|View full text |Cite
|
Sign up to set email alerts
|

Two tobacco genes induced by infection, elicitor and salicylic acid encode glucosyltransferases acting on phenylpropanoids and benzoic acid derivatives, including salicylic acid

Abstract: Two tobacco genes (TOGT) with homology to glucosyltransferase genes known to be induced by salicylic acid (SA) also responded rapidly to a fungal elicitor or to an avirulent pathogen. SA, although an efficient inducer, was shown not to be essential in the signal transduction pathway regulating TOGT gene expression during the resistance response. Recombinant TOGT proteins produced in Escherichia coli exhibited low, but significant, glucosyltransferase activity towards SA, but very high activity towards hydroxyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(122 citation statements)
references
References 32 publications
8
113
0
Order By: Relevance
“…Samsun NN (Fraissinet-Tachet et al 1998). Vogt et al (2002) showed that GT enzymatic activity prepared from cultured cells of D. bellidiformis catalyzed various flavonoid glucosides.…”
Section: Chalcone 2 -O-glucosyltransferase Activity Of Dicgt4 and Dicgt5mentioning
confidence: 99%
“…Samsun NN (Fraissinet-Tachet et al 1998). Vogt et al (2002) showed that GT enzymatic activity prepared from cultured cells of D. bellidiformis catalyzed various flavonoid glucosides.…”
Section: Chalcone 2 -O-glucosyltransferase Activity Of Dicgt4 and Dicgt5mentioning
confidence: 99%
“…The expression of some GTase genes can be induced by plant hormones, such as salicylic acid [16,17,22], auxin [16,22] or jasmonate [19], and many of them show a broad substrate specificity. Since NTGT2 also shows a broad substrate specificity, RT-PCR was performed to determine the expression pattern of NtGT2 mRNA in plant-hormone-treated tobacco cells.…”
Section: Expression Of Ntgt2 In Tobaccomentioning
confidence: 99%
“…The reported members of this GTase family are baicalein 7-O-glucosyltransferase, B5GT, salicylate-inducible GTases (IEGT [16]) and their homologues (TOGT [17]) from tobacco. B5GT was reported to be able to catalyze the glucosylation of 4'-OH or 7-OH of quercetin, but the activity against 7-OH was 10-fold lower than that against 4'-OH [15].…”
Section: Introductionmentioning
confidence: 99%
“…(D. Horvath, personal communication). It was also reported that the products of homologues genes glucosylate several kinds of phenylpropanoids, but flavonoids were not considered as possible substrates [29]. Scopoletin is known as one of the phytoalexins that can be induced by fungal infection or by treatment with plant hormones in tobacco.…”
Section: Amino-terminal Amino Acid Sequence Of the Purified Cgtasementioning
confidence: 99%